Common carotid pseudoaneurysm mimicking abscesscervical: case report - Jhonata Marcos Ferreira; Isabelle Morita; Henrique Jose Pereira de Godoy; AndréRodrigo Miquelin; José Maria Pereira Godoy (Innovative Journal of Medical and Health Sciences, 2024)
The case reported case of patient 23-year-old female referred to the Hospital de Base de São José do Rio Preto-Brazil with cervical bulging, which began 2 months ago, with suspected abscess on tomography. She then raised the urgency of a surgical approach for drainage. Therefore, laboratory tests were requested, which were within normal limits. And also, a neck angiotomography that revealed the presence of a pseudoaneurysm in the common carotid artery. He underwent endovascular treatment which progressed uneventfully and then drainage of the hematoma.Carotid artery pseudoaneurysms are rare and surgical or endovancular approaches are options that must be evaluated in each case. In this patient, the risks of each procedure were analyzed, and the endovascular option was the lowest risk option and was effective.